KETERBUKAAN INFORMASI PUBLIK MELALUI SISTEM PENGHITUNGAN (SITUNG) ONLINE HASIL PILKADA TERHADAP PENGETAHUAN, SIKAP, DAN PERILAKU MASYARAKAT DI KOTA PALU - Andi Syahruddin Alam; Muhammad Iqbal Sultan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2016)
This study aimed to investigate the correlation and effect of the public information transparency through the online counting system (SITUNG) of the regional election result on the knowledge, attitude, and behavior of the society in palu city. The research population were community members of Palu City, who were registered in the Permanent Voter List (PVL) of Palu city, 2015. The samples were chosen using the stratified random sampling technique and comprised 123 respondents. The research used the methodology or quantitative approach with the survey method, which means the explanative associative research to find the correlation and effect between one variable and another variable. The technique of data analysis was the correlation and effect analysis technique which animed to find out the correlation and effet between the independent and dependent variables – the independent variable was the public information transparency, and the dependent variables were the knowledge, attitude, and behavior. The research result indicated that there was a correlation between the public information transparency through the online counting system and the knowledge, attitude, and behavior : 0.199, 0.346, and 0.324 respectively with the weak correlation levels. Meanwhile, the effect of the public information transparency through the online counting system of the regional election was 5.6% on the knowledge, 18% on the attitude, and 20% on the behavior. This effect was caused by the low effects between the variables, while 56,4% was the effects other factors, which means that H1 was accepted and H0 was rejected; the accepted H1 comprised the correlation and the effect of the public information transparency through the online counting system of the local election on the knowledge, attitude, and behavior in Palu city. Setiap penyelenggara pemilu berkewajiban memedomani dan melaksanakan setiap butir dari asas penyelenggara pemilu. Studi ini bertujuan mengetahui hubungan dan pengaruh keterbukaan informasi publik melalui sistem penghitungan (SITUNG) online hasil Pilkada terhadap pengetahuan, sikap, dan perilaku masyarakat Kota Palu. Studi ini berjenis eksplanatif asosiatif, yaitu mencari hubungan dan pengaruh antarsatu variabel dan variabel lain. Metode dan pendekatan yang digunakan adalah metode kuantitatif dan survei. Populasi studi adalah masyarakat Kota Palu yang terdaftar didalam daftar pemilih tetap (DPT) Kota Palu tahun 2015. Penyampelan dilakukan dengan teknik acak bertingkat dengan jumlah sampel 123 responden. Teknik analisis data yang digunakan, yaitu analisis hubungan dan pengaruh antarvariabel. Hasil dari studi menunjukkan bahwa terdapat hubungan antara keterbukaan informasi publik melalui SITUNG online Pilkada dengan pengetahuan, sikap, dan perilaku masing- masing sebesar 0.199, 0.346, dan 0,324 dengan tingkat korelasi lemah. Pengaruh keterbukaan informasi publik melalui SITUNG online pilkada terhadap pengetahuan 5,6%, sikap 18%, dan perilaku 20%. Pengaruh ini diakibatkan oleh pengaruh yang rendah antar variabel. Sementara 56,4% dipengaruhi oleh faktor lain dengan menerima H1 dan menolak H0, yakni menerima hipotesis “adanya hubungan dan pengaruh keterbukaan informasi publik melalui sistem penghitungan (SITUNG) online pilkada terhadap pengetahuan, sikap, dan perilaku” masyarakat di Kota Palu.